Atraumatic restorative treatment: An 18-month field study in India - Acceptability and survival of one-surface restorations in permanent dentition - Archana Krishna Murthy; S S Hiremath (Wolters Kluwer Medknow Publications, 2013)
Objective: To assess the acceptability and survival of ART restorations on one surface carious lesions in permanent dentition among 12-13 year old government school children in Bangalore City, India. Materials & Method: A total of 181 ART restorations were placed using hand mix glass ionomer (Fuji IX) at the school premises following standard procedures. The acceptability was assessed by the presence or absence of pain or discomfort, post operative sensitivity and willingness to undergo the same type of treatment again. Evaluations of the ART restorations were done at 6,12 and 18 months. Results: Ninety one percent of children indicated that they did not feel any pain / discomfort during the procedure and 88.8% were willing to undergo the treatment again. The results of Actuarial Life-Table analysis showed that 83.7%, 76.1% and 68.7% of ART restoration survived at 6,12 and 18 months, respectively. Conclusions: Though the acceptability of ART procedure was found to be high, the survival was low.